The Spectrophotometric Multicomponent Analysis of a Ternary Mixture of Paracetamol, Aspirin, and Caffeine by the Double Divisor-Ratio Spectra Derivative Method - Reza Hajian; Ahmad Soltaninezhad (Journal of Spectroscopy)
Double divisor-ratio spectra derivative method based on the spectrophotometric data was developed for the simultaneous analysis of a ternary mixture containing paracetamol, aspirin, and caffeine, without prior separation. This method is based on the use of the derivative of the ratio spectrum obtained by dividing the absorption spectrum of the ternary mixture by a standard spectrum of a mixture of two of the three compounds in the title mixture. The concentrations of three compounds in their mixture are determined by using their respective calibration graphs which are obtained by measuring the amplitude at either the maximum or minimum wavelengths selected. The selected wavelengths for determination of aspirin, caffeine, and paracetamol are 241.5, 256, and 258.5 nm, respectively. All of the solutions adjusted to pH 11 before recording the spectra in the range of 220 to 320 nm. Also, the mathematical explanation of the procedure is illustrated. The method was applied for the assay of Excedrin containing paracetamol, aspirin, and caffeine.